Potential of Novel Bacteria from Sidoarjo Hot Mud for Controlling Potato Soft Rot Caused by Erwinia carotovora - Ahmad Muhidin; Femita Hapsari; Luqman Qurata Aini; Muhammad Akhid Syib’li; Restu Rizkyta Kusuma (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2025)
Soft rot is an important potato disease caused by the bacterial pathogen Erwinia carotovora. Although chemical bactericides are commonly used for control, biological control using antagonistic bacteria offers a promising and environmentally friendly alternative. Bacteria capable of surviving in extreme environments have been reported to show high efficiency and the ability to withstand various environmental conditions. This study aimed to isolate, evaluate the potential and activity, and identify the molecular basis of novel bacteria from Sidoarjo hot mud against E. carotovora, the causal agent of potato soft rot. The methods used included sample collection, bacterial isolation and screening, inhibition assays against E. carotovora, soft rot suppression assays on potato tubers, molecular identification using 16S rRNA gene sequencing, and antibiosis mechanism testing. Based on the research, 16 bacterial isolates were obtained, of which four isolates (BLS3, BLS6, BLS7, and BLS10) demonstrated antagonistic activity, as evidenced by the formation of clear inhibition zones on nutrient agar medium. Suppression assays further confirmed their ability to significantly reduce soft rot symptoms in potato tubers. Among these, BLS10 isolate exhibited the highest inhibition and suppression activity, with an inhibition zone of 2.03 cm and a soft rot mass of 0.52 grams. Molecular identification based on 16S rRNA gene sequencing showed that isolates of BLS3, BLS6, BLS7, and BLS10 were identified respectively as Bacillus velezensis, Bacillus methylotrophicus, Bacillus amyloliquefaciens, and Ochrobactrum intermedium. All isolates demonstrated a bacteriostatic antibiosis mechanism, indicated by turbidity in peptone water, suggesting inhibition through secondary metabolite production.